2023
DOI: 10.1161/circulationaha.122.062123
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Unibody and Non-Unibody Endografts for Abdominal Aortic Aneurysm Repair in Medicare Beneficiaries: The SAFE-AAA Study

Abstract: BACKGROUND: Concerns have been raised about the long-term performance of aortic stent grafts for the treatment of abdominal aortic aneurysms, in particular, unibody stent grafts (eg, Endologix AFX AAA stent grafts). Only limited data sets are available to evaluate the long-term risks related to these devices. The SAFE-AAA Study was designed with the Food and Drug Administration to provide a longitudinal assessment of the safety of unibody aortic stent grafts among Medicare beneficiaries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The SAFE-AAA trial is a well-executed and well-designed observational study; its limitations derive from the study design itself. We agree with Secemsky and colleagues 5 when they suggest the establishment of a prospective surveillance system in order to monitor endograft performance and graft-related adverse events. Such a quality control measure should enable better overall results after EVAR, thereby lowering the expenses associated with subsequent interventions after EVAR and leading to the natural selection of those devices and design solutions that provide the highest level of patient safety over the long term.…”
supporting
confidence: 78%
See 3 more Smart Citations
“…The SAFE-AAA trial is a well-executed and well-designed observational study; its limitations derive from the study design itself. We agree with Secemsky and colleagues 5 when they suggest the establishment of a prospective surveillance system in order to monitor endograft performance and graft-related adverse events. Such a quality control measure should enable better overall results after EVAR, thereby lowering the expenses associated with subsequent interventions after EVAR and leading to the natural selection of those devices and design solutions that provide the highest level of patient safety over the long term.…”
supporting
confidence: 78%
“…In the current issue of Circulation , Secemsky and colleagues 5 describe findings from the SAFE-AAA study (Comparison of Unibody and Non-Unibody Endografts for Abdominal Aortic Aneurysm Repair in Medicare Beneficiaries Study) on the outcomes associated with unibody and nonunibody endografts in the treatment of intact infrarenal AAA. The main goal of the SAFE-AAA study was to test whether unibody endografts are noninferior compared with nonunibody devices in terms of a composite primary outcome of post–index procedure aneurysm rupture, aortic reintervention, or all-cause mortality.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The investigation by Wang and colleagues 6 comes on the heels of 2 recent studies evaluating the safety of AFX stent grafts. 7,8 Despite using methodologies with different data sources, patient populations, and analytical approaches, all 3 groups found that the AFX stent grafts were associated with higher safety risks than were other EVAR devices. Nonetheless, each study illustrated key limitations of current mechanisms for postmarket surveillance using claims or registry data.…”
mentioning
confidence: 99%